Investigating a Conservation Area Based on Tsunami Hazard Mapping in Landuse Planning of Sand Dune Parangtritis Area, Yogyakarta, Indonesia: Investigating a conversation area based on Tsunami Hazard, Yogyakarta, Indonesia - Putri, Ratih Fitria; Wibirama, Sunu; Mardiatno, Djati; Giyarsih, Sri Rum; Sumantyo, Josaphat Tetuko Sri (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The Southern part of Java Island is highly risked from natural disaster, particulary tsunami. In this research, we investigated a conservation area of the southern part of Yogyakarta (Bantul Regency), Indonesia, namely Parangtritis. Sand dune in Parangtritis is a natural barrier for tsunami threat. Material loss caused by tsunami can be reduced by identifying natural barrier of sand dune through tsunami hazard zones. We propose a method to investigate changes of sand dune condition by simulating the tsunami inundation hazard impact and implementing a remote sensing application. A water depth of tsunami model scenario was used to estimate the tsunami inundation zone. The tsunami modeling used Shuttle Radar Topography Mission (SRTM) data to build Digital Elevation Model (DEM) data. Topographical map and ALOS imagery were used to analyze land coverage. Based on our simulation, the tsunami tends to surge toward the southeast direction with 30 m of elevation. Material loss due to tsunami is catastrophic; hence more extensive sand dune conservation area is required. This research provides a tsunami hazard map and a sand dune conservation map based on our simulation. In future, our research might be used as a guideline for development of policy to develop and to protect sand dune conservation area.